Antara Anarki dan Demokrasi: Masalah Kekerasan Politik di Indonesia - Cornelis Lay (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
A critical analysis of how the New Order state has established its power basis and how the power has been utilised and abused leads us to conclude that anarchy is a rational response to the state's actions. Democracy, as a non-violent scheme of conflict management, is hampered by the formation of consolidated anarchy. Democratization leaves us with an agenda for mollifying violent.